Validation of the International Adjustment Disorder Questionnaire in Israel and Switzerland. (20th January 2022) - Levin, Yafit; Bachem, Rahel; Hyland, Philip; Karatzias, Thanos; Shevlin, Mark; Ben‐Ezra, Menachem; Maercker, Andreas
Abstract: The ICD‐11 has introduced a new conceptualization of adjustment disorder (AjD) as a stress response syndrome with core symptoms of preoccupations and failure to adapt to the stressor. The current study aimed to assess the reliability and validity of the International Adjustment Disorder Questionnaire (IADQ) in two culturally distinct samples from Israel and Switzerland. Two samples were recruited in Israel ( N  = 1142) and Switzerland ( N  = 699) during the initial stages of the COVID‐19 pandemic. Confirmatory factor analysis indicated that a correlated two‐factor model provided an excellent fit to the Israeli and Swiss sample data. The IADQ scores correlated strongly with another measure of AjD symptoms and with symptoms of depression, anxiety, acute stress and negative emotions, whereas correlations with posttraumatic stress disorder, complex posttraumatic stress disorder and positive emotions were weaker. In the Swiss sample, 18.8% met diagnostic criteria for probable AjD and 10.2% in the Israeli sample. The current study provides the first evidence of the validity of the German and Hebrew versions of the IADQ and can be used for the screening of this debilitating condition.